Contact-induced lexical development in Yupik and Inuit languages - Berge, Anna; Kaplan, Lawrence (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractLexical change in Yupik and Inuit languages was relatively slow until the period of widespread cultural change brought about by contact with Europeans over the past few centuries, probably because there had been little earlier contact with other language families. The colonial period brought various groups to the Arctic and different waves of language contact, primarily with Danish, French, English, and Russian. Lexical borrowing has been significant, and old borrowings, often the result of early trade, can be distinguished from later ones and often pertain to food, tobacco, tools, fabric and other areas where new goods were introduced. Later borrowings came about largely when European political structures were set up and may be less thoroughly integrated phonologically than older borrowings. Numbers of borrowings can be taken to reflect the extent of the foreign contact, as is clearly the case with Russian words in Alaskan languages, most numerous in Aleut, which had the most sustained Russian presence. New religious terms to describe Christianity came into the languages during the colonial period, sometimes as borrowings, but also as relexicalizations of old words pertaining to shamanism. A third means of lexical expansion is coinage, where new terms are invented based on native roots and suffixes. The languages and dialects may thus develop words for the same object or concept by borrowing from different European languages, by relexicalizing an old word, or by coining a new one, with a different result in each case. Different sources for new lexical items have resulted in an important level of differentiation among the languages, and this differentiation needs to be recognized.